Soil ecology and management - Whalen, Joann K.; Sampedro, Luis. (Cambridge, MA : CABI, 2010)
"Soil ecology is the study of interactions between the physio-chemical components of the soil and organisms living within the soil. Humans are highly dependent upon the soil ecosystem, which provides food, fibre, fuel and ecological services, such as the recycling of atmospheric gases. It is therefore important to understand the function and nature of the soil ecosystem in order to predict and mitigate the long-term consequences of present-day actions." "Soil Ecology & Management describes the organisms inhabiting the soil, their functions and interactions and the dimensions of human impact on the activity of soil organisms and soil ecological function. Chapters cover basic soil characteristics and biogeochemical cycling, key soil flora and fauna, community-level dynamics (soil foodwebs) and the ecological and pedological functions of soil organisms."--Jacket.
Keywords: Soil ecology; Soil management